Analisis Nilai Kehijauan Berdasarkan Pengukuran Komputasi dan Persepsi Manusia pada Ruang Terbuka Hijau di Pekanbaru, Riau - Septiantoro, Ripki; Zain, Alinda Fitriany Malik; Pribadi, Didit Okta (Jurnal Lanskap Indonesia, 2025)
Along with economic development, there have been changes in land use, resulting in forests, green space, and agricultural land conversion into residential and industrial/commercial areas in many cities. Due to the reduction in green space, efforts have been made in urban planning to restore greenery around residential neighborhoods in many metropolitan areas. The government has made several efforts to regulate urban development planning to ensure sustainability. One of the efforts is the implementation of Law No. 26 of 2007, which mandates that at least 30% of the city's area must be designated as Green Open Space (GOS). The Green City Development Program (P2KH) implemented the law in several cities, including Pekanbaru, the capital of Riau Province, Indonesia. This study aims to measure the impact of the Green City program implementation on the increase or decrease in the area of GOS in Pekanbaru City and and to analyze the quality of Greenery Values of GOS in Pekanbaru City based on human perception and computational measurement. This research analyzes Land Use Cover Change (LUCC) post-P2KH in Pekanbaru and compares mapping methods with human perceptions of greenery at randomly selected locations. Using QGIS 3.36.0 and the Maximum Likelihood Classification (MLC) method, the study found that the decline in Green Open Spaces in Pekanbaru has leveled off from 11.85% before P2KH to 6.59% after P2KH, and the increase in built-up areas has slowed from 12.58% to 6.2%. Computational measurements, such as NDVI, and human perceptions reveal that Pekanbaru's GOS need improvements in safety, comfort, aesthetic quality, and biodiversity. This research indicates that the P2KH has mitigated the high rate of land cover and land use changes in Pekanbaru.